Comparisons of segment-specific toxicity of platinum-based agents and cadmium using S1, S2, and S3 cells derived from mouse kidney proximal tubules. (September 2021) - Fujishiro, Hitomi; Taguchi, Hiroki; Hamao, Satoko; Sumi, Daigo; Himeno, Seiichiro
Abstract: Renal toxicants such as cisplatin and cadmium cause segment-specific damages in kidney proximal tubules. Recently, we established an in vitro experimental system for evaluating segment-specific toxicity and transport of chemicals using immortalized S1, S2, and S3 cells derived from the S1, S2, and S3 regions of mouse kidney proximal tubules. In the present study, we examined the toxicity and accumulation of cisplatin, carboplatin, oxaliplatin, and cadmium in S1, S2, and S3 cells. We found that not only cisplatin but also carboplatin and oxaliplatin exhibited higher lethal toxicity in S3 cells than in S1 and S2 cells. At sublethal doses, cisplatin showed delayed induction of Kim-1 and clusterin on days 3 and 6, which may reflect the latent renal toxicity of cisplatin in vivo . The high sensitivities of S3 cells to the platinum-based agents were not due to the high accumulation of Pt in S3 cells. Exposure to cadmium resulted in similar toxicity among these cells, suggesting that S3 cells were not sensitive to any renal toxicants. Thus, the utilization of S1, S2, and S3 cells may provide a useful tool for the in vitro evaluation of the proximal tubule segment-specific toxicity of chemicals. Highlights: Cisplatin causes renal damage especially in S3 segment of proximal tubules in vivo . Cytotoxicity of Pt agents and Cd was compared among cultured S1, S2 and S3 cells. Cisplatin, oxaliplatin and carboplatin showed the highest lethal toxicity in S3 cells. Cisplatin induced Kim-1 and clusterin in S3 cells in a delayed manner as in vivo . S1, S2, and S3 cells are useful for assessing segment-specific renal toxicity in vitro .